1976
DOI: 10.2307/1128811
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Study of the Effects of High-Risk Factors on Performance on the Brazelton Neonatal Assessment Scale

Abstract: The Brazelton Neonatal Assessment Scale was administered to 52 newborn infants. A factor analysis revealed 2 main factors, 1 along an attention-orientation dimension, the other relating to temperament arousal. A stepwise multiple linear regression analysis showed that the attention-orientation factor was related to birth weight, age of the mother, and sex and race of the baby. The only variable related to the temperament-arousal factor was 5-min Apgar scor. The study, although exploratory, demonstrates the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…The Neonatal Behavioural Assessment (NBAS) was administered to the intensive sample at 5 weeks after birth. The NBAS is a standardized measure designed to assess orienting, motor and emotion regulatory processes during the first weeks of life (Brazelton & Nugent 1995, Lester et al 1976). It is conducted by a trained administrator who carries out, in a prescribed sequence, a range of manoeuvres, designed to elicit the infant's optimal orienting and motor performance, and emotional responses to mildly aversive procedures such as undressing or being brought from lying to sitting.…”
Section: Infant Negative Emotionalitymentioning
confidence: 99%
“…The Neonatal Behavioural Assessment (NBAS) was administered to the intensive sample at 5 weeks after birth. The NBAS is a standardized measure designed to assess orienting, motor and emotion regulatory processes during the first weeks of life (Brazelton & Nugent 1995, Lester et al 1976). It is conducted by a trained administrator who carries out, in a prescribed sequence, a range of manoeuvres, designed to elicit the infant's optimal orienting and motor performance, and emotional responses to mildly aversive procedures such as undressing or being brought from lying to sitting.…”
Section: Infant Negative Emotionalitymentioning
confidence: 99%
“…Of these, 7 studies (Brown et al, 1975;Brown & Fredrickson, 1977;Korner, Kraemer, Haffner & Thoman, 1974;Milewski & Siqueland, 1975;Rieser, Yonas & Wikner, 1976;Rose et al, 1978;Ruff & Halton, 1978) found no gender differences; the remaining 4 (Feldman, Brody & Miller, in press;Hwang, 1978;Jacklin, Snow, & Maccoby, in press: Phillips et al, 1978) have found no consistent results favoring either males or females. None of the 6 studies using siandardized tests has found consistent gender differences (Aleksandrowici & Aleksandrowicz, 1974;Horowitz, Ashton, Culp, Gaddis, Levin & Reichmann, 1977;Lester, Als & Brazelton, in press;Lester, Emory, Hoffman & Eitzman, 1976;Rosenblith, 1974;Sigman, Kopp, Parmelee & Jeffrey, 1973). Similarly, few gender differences in state have been reported, and those that have are inconsistent (Feldman et al, in press;Jacobs & Friedman, 1979;Korner & Thoman, 1973;Phillips et al, 1978;Smith and Steinscheider, 1975).…”
Section: Resultsmentioning
confidence: 99%
“…Item-by-item comparisons across the individual NBAS items gave way to approaches based on factor analysis (e.g., Azuma, Malee, Kavanagh, & Deddish, 1991;Jacobson et al, 1986;Lester et al, 1976;Sostek, 1985), but it was Lester's seven-cluster system that became the most widely used system among researchers (Lester, 1984;Mayes, Granger, Frank, Schottenfeld, & Bornstein, 1993;Sagiv et al, 2007). Item-by-item comparisons across the individual NBAS items gave way to approaches based on factor analysis (e.g., Azuma, Malee, Kavanagh, & Deddish, 1991;Jacobson et al, 1986;Lester et al, 1976;Sostek, 1985), but it was Lester's seven-cluster system that became the most widely used system among researchers (Lester, 1984;Mayes, Granger, Frank, Schottenfeld, & Bornstein, 1993;Sagiv et al, 2007).…”
Section: The Nbas -Contents and Scoringmentioning
confidence: 99%